2022
DOI: 10.3389/fnins.2022.1000716
|View full text |Cite
|
Sign up to set email alerts
|

Emotion recognition based on multi-modal physiological signals and transfer learning

Abstract: In emotion recognition based on physiological signals, collecting enough labeled data of a single subject for training is time-consuming and expensive. The physiological signals’ individual differences and the inherent noise will significantly affect emotion recognition accuracy. To overcome the difference in subject physiological signals, we propose a joint probability domain adaptation with the bi-projection matrix algorithm (JPDA-BPM). The bi-projection matrix method fully considers the source and target do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…A novel method based on substructure-based joint probability domain adaptation was created by Fu et al [15] to lessen the detrimental effects of noise on physiological inputs. Pusarla et al [16] improved upon earlier approaches in terms of emotion identi cation accuracy by employing a local mean decomposition methodology for EEG signals.…”
Section: Literature Surveymentioning
confidence: 99%
“…A novel method based on substructure-based joint probability domain adaptation was created by Fu et al [15] to lessen the detrimental effects of noise on physiological inputs. Pusarla et al [16] improved upon earlier approaches in terms of emotion identi cation accuracy by employing a local mean decomposition methodology for EEG signals.…”
Section: Literature Surveymentioning
confidence: 99%
“…The authors demonstrated that the learned mappings reflected prior knowledge on the semantic relationships between domains, making the MSADA a powerful tool for exploratory activity data analysis; the proposed multisource domain adaptation approach achieved a 2% and a 13% improvement in accuracy on both the OPPORTUNITY dataset and the DSADS dataset, respectively. In [221], the authors proposed a new method called joint probability domain adaptation with a bi-projection matrix algorithm (JPDA-BPM) to overcome the challenge of collecting enough labeled data for emotion recognition based on physiological signals, which is time-consuming and expensive. The proposed method considered the differences in feature distributions between the source and target domains, which improved the algorithm's performance.…”
Section: Domain Adaptationmentioning
confidence: 99%
“…For the MSP-IMPROV dataset, the suggested method obtained results that are considered to be state-of-the-art. Using 3D convolutional neural networks, the authors [17] proposed a transfer learning approach for multimodal emotion recognition (CNNs). For the recognition of facial expressions, they used pre-trained models and then fine-tuned them using their own dataset.…”
Section: Research Articlementioning
confidence: 99%